Effect of polishing time on distribution of monomeric anthocyanin, iron and zinc content in different grain layers of four Thai purple rice varieties - Benjavan Rerkasem (2018)
© 2015 Friends Science Publishers. This study aimed to establish how distribution of nutrients might vary in surface grain layers of purple rice by evaluating their monomeric anthocyanin, Fe and Zn concentration affected by polishing. Concentration of monomeric anthocyanin, Fe and Zn, grain dimension and pigmentation intensity of 4 purple rice varieties (KD, high monomeric anthocyanin; KH, high Fe; LP, high Zn- monomeric anthocyanin; BI, low monomeric anthocyanin-Fe-Zn) from Thailand was determined after polishing five times. Pigmentation reduced in all varieties after 15 s polishing, while monomeric anthocyanin concentration declined in BI and KD but increased in KH and LP. Monomeric anthocyanin ultimately declined in all varieties with longer polishing, but there was no correlation between monomeric anthocyanin concentration and pigmentation intensity at 0 to 30 s. Micronutrients Fe and Zn concentration was increasingly depressed with longer polishing, although the effect on Zn was relatively less. Monomeric anthocyanin, Fe and Zn were distributed differently in successive layers of rice grain removed by polishing, with major varietal difference for monomeric anthocyanin. In some varieties, highest monomeric anthocyanin concentration was in the outer-most grain layer, but was richest below the surface in others. The highest concentration of Fe and Zn were also in outer-most layer, although more Zn was distributed deep in endosperm and most of Fe was removed after 30 s. Such variation should be taken into consideration in efforts to retain or recover potentially valuable nutrients from the grain of purple rice.